Estimation of Kidney Function in Patients With Multiple Myeloma: Implications for Lenalidomide Dosing. Issue 1 (January 2023) - Salama, Engie; Lam, Stepfanie; Gonsalves, Wilson I.; Tzachanis, Dimitrios; Momper, Jeremiah D.; M. Saunders, Ila
Background: Lenalidomide is an immunomodulatory drug used to treat multiple myeloma that requires renal dosing adjustment based on Cockcroft-Gault (CG). Various equations to estimate kidney function exist and pose a potential issue with lenalidomide dosing. Objective: The objective of this analysis was to evaluate the impact of estimating kidney function in newly diagnosed multiple myeloma patients with CG, Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) and their potential impact on lenalidomide dosing. Methods: Data from 1121 multiple myeloma patients at the time of diagnosis acquired from the Mayo Clinic were used to calculate creatinine clearance (CrCl) using Cockcroft-Gault with actual body weight (CGABW ), ideal body weight (CGIBW ), or adjusted body weight (CGAdjBW ); MDRD; and CKD-EPI for each subject. Discordances in dosing were then analyzed, and lenalidomide exposure was calculated for each subject to assess impact on pharmacokinetics of lenalidomide for patients who received discordant doses. Results: Overall, approximately 16% of patients received a discordant dose when using MDRD or CKD-EPI instead of CGABW . The most common dose discordance was the decrease of a full dose of lenalidomide 25 mg when using CGABW down to 10 mg and when using MDRD or CKD-EPI with 53.8% to 55.6% of all discordances in this category. When assessing different body weights, the most common discordance was a decrease from 25 to 10 mg when using CGIBW instead of CGABW ; the same trend was observed when using CGAdjBW instead as well. Patients were also at risk of over- or underexposure based on area under the concentration versus time curve (AUC) for discordant dosing. Conclusion and Relevance: A significant proportion of patients are at risk of under- or overdose of lenalidomide if CKD-EPI or MDRD are used instead of CGABW . Physicians should use CGABW when estimating renal function to dose lenalidomide.